Association between single and multiple cardiometabolic diseases and depression: A cross-sectional study of 391,083 participants from the UK biobank - Gong, Li; Ma, Tianqi; He, Lingfang; Lin, Guoqiang; Zhang, Guogang; Cheng, Xunjie; Luo, Fanyan; Bai, Yongping (Frontiers in Public Health, 2022)
Background Individual cardiometabolic diseases (CMDs) are associated with an increased risk of depression, but it's unclear whether having more than one CMD is associated with accumulative effects on depression. We aimed to assess the associations between CMDs and depression and determine the accumulative extent. Methods In this cross-sectional study based on UK Biobank, participants with available information on CMDs and depression were enrolled. The history of CMDs was derived from self-reported medical history and electrical health-related records. Depression status was assessed by the aggregation of self-reported history and antidepressant use, depression (Smith), and hospital inpatient diagnoses. Logistic regression models were fitted to assess the association between the number or specific patterns of CMDs and depression and to test the accumulative effect of CMD number, adjusting for confounding factors. Results 391,083 participants were enrolled in our analyses. After multivariable adjustments, CMDs of different number or patterns were associated with a higher risk of depression compared with the reference group (all P < 0.001). In the full-adjusted model, participants with one [odds ratio (OR) 1.26, 95% confidence interval (CI) 1.23–1.29], two (OR 1.50, 95% CI 1.44–1.56), and three or more (OR 2.13, 95% CI 1.97–2.30) CMD(s) had an increased risk of depression. A significant, accumulative dose-related relationship between the number of CMDs and depression was observed (OR 1.25, 95% CI 1.24–1.27). The dose-dependent accumulative relationship was consistent in stratified analyses and sensitivity analyses. Conclusions CMDs were associated with a higher risk of depression, and there was an accumulative relationship between CMD number and depression.